The Influence of Self-Efficacy, Compensation, and Competence on the Performance of Kindergarten Teachers at the Merawang Sub-District Level - Aprilia, Mia; Reniati, Reniati; Nurwasya, Nurwasya (International Journal of Magistravitae Management, 2024)
This study is motivated by the suboptimal performance of kindergarten teachers, which is influenced by various factors affecting their ability to achieve optimal performance. The purpose of this study is to examine and analyze the influence of self-efficacy, compensation, and competence on the performance of kindergarten teachers at the Merawang Sub-District Level. This research is classified as descriptive quantitative research. The study involved 46 respondents selected using the saturated sampling method. The data were analyzed using the multiple linear regression analysis model. The results show that self-efficacy, compensation, and competence each have a positive and significant effect on the performance of kindergarten teachers at the Merawang Sub-District Level. Furthermore, the simultaneous test results indicate that self-efficacy, compensation, and competence collectively have a positive and significant effect on the performance of kindergarten teachers at the Merawang Sub-District Level.